A welfare analysis of the electricity transmission regulatory regime in Germany - Claudia Kemfert; Friedrich Kunz; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We analyze the current regulatory regime for electricity transmission in Germany, which combines network planning with both cost-plus and revenue-cap regulations. After reviewing international experiences on transmission investment, we first make a qualitative assessment of the overall German regime. The German TSOs have in general incentives to overinvest and inefficiently inflate costs. We further develop two models to analyze the transmission planning process. In the first model there is no trade-off between transmission expansion and generation dispatch. This is a modeling set-up similar to the one actually used in the German transmission planning (Netzentwicklungsplan). A second model alternatively allows for such a trade-off, and thus represents an optimal way of transmission network planning. Simulations with the two models are carried out and compared so as to illustrate the amount of excessive transmission capacity investment and welfare losses associated with the current regime.
Keywords: L50; L94; Q40; 330; transmission planning; nodal prices; congestion management; electricity; Germany